2000
DOI: 10.1016/s1010-7940(00)00429-2
|View full text |Cite
|
Sign up to set email alerts
|

Limited right anterolateral thoracotomy for mitral valve surgery

Abstract: The cosmetic appearance in the test group was excellent and the patients' wounds were scarcely apparent in the female patients. The study demonstrates the efficacy and safety of this older technique, with excellent cosmetic results and no additional cost or risk to the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 9 publications
3
28
1
Order By: Relevance
“…In a study, El-Fiky et al (2000)observed that the mean age of study population was 22 ± 10 years, which is comparable with the current study. 9 However, Ganie et al (2013) and Aybek et al (2006) found the mean age was 44.4 ± 8.2 and 56 ± 14 years respectively in right anterolateral thoracotomy, which is higher with the current study. 6, 11 Similarly, in another study Grossiet al was found the mean age 55.3 ± 17.2 years in standard sternotomy approach, which also higher with the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…In a study, El-Fiky et al (2000)observed that the mean age of study population was 22 ± 10 years, which is comparable with the current study. 9 However, Ganie et al (2013) and Aybek et al (2006) found the mean age was 44.4 ± 8.2 and 56 ± 14 years respectively in right anterolateral thoracotomy, which is higher with the current study. 6, 11 Similarly, in another study Grossiet al was found the mean age 55.3 ± 17.2 years in standard sternotomy approach, which also higher with the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…The scar usually is covered by breast tissue in female patients. Moreover, complications related to sternotomy, as sternal infection or bleeding, is avoided with this technique [3,5]. One of the principal concern about less invasive surgery is the balance between limited exposure and safety of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, was suggested that a limited anterolateral thoracotomy should be preferred to an extended lateral thoracotomy, in order to minimize postoperative pulmonary complications, because it provides a good operative exposure and preserves the integrity of thoracic cage [3][4][5]. Besides, limited thoracotomy is associated to less infection occurrence, less bleeding and earlier postoperative recovery [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered that, in children, this approach does not impact or change in the development of the chest, the pectoral muscle and breast tissue, maintaining the continuity and integrity of the bony part of the chest. It would be a surgical option to prevent the installation of the deformity called pigeon breast [34][35][36][37][38].…”
Section: Cardiac Surgery Postoperative (Ccpo)mentioning
confidence: 99%